Governing the design of national REDD+: an analysis of the power of agency - Brockhaus, Maria; Gregorio, M. di; Mardiah, S. (Elsevier, 2014)
This paper investigates how three aspects of governance systems, namely the policy context, the influence of key agents and their discursive practices, are affecting national-level processes of policy design aimed at REDD +, reducing emissions from deforestation and forest degradation in developing countries; and the role of conservation, sustainable management of forests and enhancement of forest carbon stocks in developing countries. We conducted analysis in six REDD + countries (Brazil, Cameroon, Indonesia, Nepal, Papua New Guinea and Vietnam). The paper combines three methods: policy analysis, media-based discourse analysis and policy network analysis. The paper shows that policies both within and outside the forestry sector that support deforestation and forest degradation create path dependencies and entrenched interests that hamper policy change. In addition, most dominant policy coalitions do not challenge business-as-usual trajectories, reinforcing existing policy and political structures. No minority policy coalitions are directly tackling the root causes of deforestation and forest degradation, that is, the politico-economic conditions driving them. Instead they focus on environmental justice issues, such as calls for increased participation of indigenous people in decision-making. Only in two of the six countries are these transformational change coalitions vocal enough to be heard, yet to exercise their agency effectively and to support more substantial reforms, these coalitions would need the participation of more influential policy actors, particularly state agencies that have the authority to make binding decisions about policy. Furthermore, discourses supporting transformational change would need to be reflected in institutional practices and policy decisions.